2003
DOI: 10.1136/bjo.87.6.667
|View full text |Cite
|
Sign up to set email alerts
|

Extracapsular cataract surgery compared with manual small incision cataract surgery in community eye care setting in western India: a randomised controlled trial

Abstract: Aim: To study "manual small incision cataract surgery (MSICS)" for the rehabilitation of cataract visually impaired and blind patients in community based, high volume, eye hospital setting; to compare the safety and effectiveness of MSICS with conventional extracapsular cataract surgery (ECCE). Methods: In a single masked randomised controlled clinical trial, 741 patients, aged 40-90 years, with operable cataract were randomly assigned to receive either MSICS or ECCE and operated upon by one of eight participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
110
7
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(129 citation statements)
references
References 9 publications
11
110
7
1
Order By: Relevance
“…11 A randomised trial showed that 48% of patients achieved an unaided vision of 6/18 or better 6 weeks after SICS compared to 37% following conventional ECCE. 28 The same trial also demonstrated that SICS was no more costly. Including fixed costs, the cost per operation was $15.82 for standard ECCE and $15.68 for SICS.…”
Section: Surgerymentioning
confidence: 91%
See 1 more Smart Citation
“…11 A randomised trial showed that 48% of patients achieved an unaided vision of 6/18 or better 6 weeks after SICS compared to 37% following conventional ECCE. 28 The same trial also demonstrated that SICS was no more costly. Including fixed costs, the cost per operation was $15.82 for standard ECCE and $15.68 for SICS.…”
Section: Surgerymentioning
confidence: 91%
“…28,29 However, with increasing experience, it is possible to perform SICS in well over 90% of eyes. 30 There are no published randomised trials comparing SICS with phacoemulsification.…”
Section: Surgerymentioning
confidence: 99%
“…Gogate et al 14 , reported iridodialysis in 2 cases (0.56%) out of total 358 manual SICS cases. Our study is in accordance with the above study.…”
Section: Superior Iridodialysismentioning
confidence: 99%
“…Antibiotic and steroid administration is similar to that of ECCE. MSICS was demonstrated to show better uncorrected postoperative vision when compared to ECCE [38]. Even when final visual recovery is similar in MSICS and ECCE, eyes in the small incision group tend to have significantly faster recovery [39].…”
Section: Manual Small Incision Cataract Surgerymentioning
confidence: 99%